IMPLEMENTASI METODE SIMPLE ADAPTIVE WEIGHTED PADA SPK UKT UNIVERSITAS PALANGKA RAYA - Parhusip, Jadiaman (Universitas Palangka Raya, 2016)
A special UKT decision team of University of Palangkaraya has used calculation application system based on desktop to calculate and group UKT. Data which are necessary from each university student are used to calculate the amount of the UKT by the application. A calcutating and grouping system is needed to solve problems in entering large amount of data. A decision supporting system (SPK) is made to increase work efectiveness and shorten time of processing data in grouping or selecting the amount of the UKT which will be charged to each new student of the university, especially regular students. There are some features in this system; calculating data, grouping the university students to each UKT group which is based on number of the students and printing or showing data which are groups of students based on the amount o the UKT. Grouping process is implemented in the first semester in the first year. SPK approach which is used is SAW method (Simple Adaptive Weighted).